(untitled) (Rudarsko-geološko-naftni zbornik, 2015)
A preliminary assessment of the capacity of regional geological storage in the western part of the Sava Depression was based on data obtained from several deep exploration wells. The Poljana Sandstones represent a regional deep sandstone body, in most parts saturated with water, with promising underground facilities for the storage of CO₂ in the study area. Poljana Sandstones (member of Kloštar-Ivanić Formation bounded between E-log markers Rνand Z’) have favourable petrophysical properties and are situated at reasonable depths. According to previous investigations, at depths greater than 800 meters supercritical conditions of temperature and pressure CO₂ are achieved, which ensures easy and safe injection into storage underground facilities. For the creation of a model in Petrel software, various data was used, including the distribution of CO₂ density, porosity, effective thickness and the relative depth of sandstone. Spatial distribution of porosity was made regarding neutron porosity logs. The most important parameter in the estimate of storage capacity is effective thickness, defined by the interval between E–log markers Rν and Z’. Hence, the effective thickness was used for top and bottom surface of sandstones. Density of CO₂ was created according to their spatial distribution regarding the depth and the temperature. The capacity of CO2 storage was calculated by the volumetric method. The use of a calculated Petrel model can subsequently determine the amount of CO₂ storage in the underground facilities of the study area.